2017
DOI: 10.1021/acs.nanolett.7b02867
|View full text |Cite
|
Sign up to set email alerts
|

Significantly High Thermal Rectification in an Asymmetric Polymer Molecule Driven by Diffusive versus Ballistic Transport

Abstract: Tapered bottlebrush polymers have novel nanoscale polymer architecture. Using nonequilibrium molecular dynamics simulations, we showed that these polymers have the unique ability to generate thermal rectification in a single polymer molecule and offer an exceptional platform for unveiling different heat conduction regimes. In sharp contrast to all other reported asymmetric nanostructures, we observed that the heat current from the wide end to the narrow end (the forward direction) in tapered bottlebrush polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…and Tian simulated tapered bottlebrush polymer by MD and obtained R with a maximum value of 0.7 [21]. Similar length dependent R was observed in their work, which was attributed to the ballistic transport.…”
Section: Thermal Rectificationsupporting
confidence: 77%
See 2 more Smart Citations
“…and Tian simulated tapered bottlebrush polymer by MD and obtained R with a maximum value of 0.7 [21]. Similar length dependent R was observed in their work, which was attributed to the ballistic transport.…”
Section: Thermal Rectificationsupporting
confidence: 77%
“…demonstrated that in a superlattice K is not merely an intrinsic property of the interface but also positively correlated to the phonon mean free paths (MFPs) of materials in the interfaces [44]. In the ballistic thermal transport of 1D nanosystems, the effective MFPs are greatly determined by the lengths of CNT [21,45]. For example, based on the Matthiessen law for diffusive-ballistic transport [45,46], the effective MFP of CNT, λeff, can be expressed as , where λ0 is the intrinsic MFP and L is the length of CNT.…”
Section: Study Of Interfacial Thermal Conductance Through Mbsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCFF, a class II potential which includes anharmonic bonding terms, 20,21 is intended for applications in polymers and organic material. 6,[22][23][24] The size of supercells used to calculate k x in this study also can be found in Table I. We intentionally set the supercells of these single-chain polymers to be large enough to rule out size effects.…”
Section: Methodsmentioning
confidence: 99%
“…By rectifying heat currents, thermal rectification has substantial implications for thermal transport, for example, by allowing energy systems to dissipate heat to their surroundings but simultaneously protecting them from damage when the surrounding temperature is too high. Although several mechanisms based on thermal expansion 7 , asymmetric nanostructures and mass loading [8][9][10][11][12][13] , solid-liquid phase change 14,15 , solid-solid phase transition [16][17][18][19][20][21] and bi-material interface 22 were demonstrated for realizing thermal rectification, it has remained a significant challenge to achieve a large and tunable rectification effect, which generally requires either macroscale size or large temperature bias.…”
mentioning
confidence: 99%